TATA KELOLA SISTEM PENJAMINAN SIMPANAN PERBANKAN DI INDONESIA - Sjafruddin, Sjafruddin; Iskandar, Iskandar (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2020)
The ratification of Law Number 24 of 2004 concerning the Deposit Insurance Corporation (LPS) marks the formal process of institutionalizing the deposit insurance system in Indonesian banking. After the banking systemic crisis in 1997 that hit various countries including Indonesia, the government made various stabilization and reform policies in the financial sector to improve the banking system. The blanket guarantee policy for bank customer deposits in 1998 with no limits (blanket guarantee) restored public confidence in banks, but on the other hand this guarantee also created a moral hazard risk for banks. The existence of the LPS ended the unlimited deposit insurance system by limiting the guarantee in the form of a deposit insurance limit and a guaranteed interest rate known as the LPS interest rate. This article attempts to describe and analyze the institutionalization process and governance process in the deposit insurance system in Indonesia. The results show that the process of institutionalizing the deposit insurance system in Indonesia is carried out in stages by assessing banking risk taking and public perceptions of the banking industry in Indonesia. In the governance process, the LPS carries out its function as guarantor of deposits of depositors, LPS is tasked with determining and formulating policies for implementing deposit insurance and implementing deposit insurance. LPS makes payment of guarantee claims to depositors from banks whose business licenses have been revoked as long as they meet the requirements stipulated by the LPS Law. Keywords: Deposit Insurance Agency, Institutionalization, Governance. Abstrak Lahirnya Undang-Undang Nomor 24 Tahun 2004 tentang Lembaga Penjamin Simpanan (LPS) menandai proses formal institusionalisasi sistem penjaminan simpanan pada perbankan di Indonesia. Setelah Krisis sistemik perbankan tahun 1997 yang melanda berbagai negara termasuk Indonesia, pemerintah membuat berbagai kebijakan stabilisasi dan reformasi di sektor keuangan guna menyehatkan sistem perbankan. Kebiijakan penjaminan terhadap jumlah simpanan nasabah perbankan pada tahun 1998 dengan tanpa batasan (blanket guarantee) mengembalikan kepercayaan masyarakat terhadap perbankan, namun disisi lain jaminan tersebut juga menimbulkan risiko moral hazard bagi perbankan. Keberadaan LPS mengakhiri sistem penjaminan simpanan tanpa batas dengan membatasi penjaminan dalam bentuk limit penjaminan simpanan dan suku bunga yang dijamin yang dikenal dengan suku bunga LPS. Artikel ini mencoba memaparkan dan menganlisa proses institusionalisasi dan proses tata kelola (governance) pada sistem penjaminan simpanan di Indonesia. Hasilnya menunjukkan bahwa proses institusionalisasi sistem penjaminan simpanan di Indonesia dilakukan secara bertahap dengan menilai risk taking perbankan dan persepsi masyarakat terhadap industri perbankan di Indonesia. Dalam proses tata kelola, LPS menjalankan fungsinya sebagai penjamin simpanan deposan, LPS bertugas menetapkan dan merumuskan kebijakan pelaksanaan penjaminan simpanan serta melaksanakan penjaminan simpanan. LPS melakukan pembayaran klaim penjaminan kepada deposan dari bank yang dicabut izin usahanya sepanjang telah memenuhi persyaratan yang telah ditetapkan oleh UU LPS. Kata kunci: Lembaga Penjamin Simpanan, Institusionalisasi, Tata Kelola.